Initiating a Full Fulfilment Curriculum-Based Deep Learning: Integration of Knowledge and Character in Learning - Aulia Fitri; Khairul Amin; Zuhri Tauhid; Aulia Ramadona; Wismanto (Jurnal PAJAR (Pendidikan dan Pengajaran))
An effective educational curriculum must integrate the development of students' knowledge and character, especially for facing the challenges of the modern era. Based on these needs, the full fulfilment curriculum was developed to combine aspects of academic knowledge with character formation through deep learning approaches, namely Mindful Learning, Meaningful Learning, and Joyful Learning. The present study aims to explore the effectiveness of the full fulfilment curriculum in improving the learning quality and shaping students' character through positive behaviours, such as healthy living habits and society. This approach is designed so that students not only receive theoretical knowledge, but also engage in holistic self-development, which includes physical, social, and emotional aspects. This research uses a descriptive qualitative method through observation, interviews, and document analysis as data collection. The sample consisted of students and teachers at several schools, implementing this curriculum. Data analysis was carried out by referring to the theories of character education and active learning approaches to ensure the relevance and success of the curriculum. The research results show that the full fulfilment curriculum is effective in helping students to learn deeply and forming good habits, such as waking up early, worshipping, exercising, loving to study, eating healthy, socialising, and sleeping on time. In addition, five main strategies—counselling guidance training, teacher competency improvement, character building, appointment of BK teachers, and a nutritious lunch program—play a significant role in supporting the implementation of this curriculum. The full fulfilment curriculum offers a holistic approach and emphasizes a balance between knowledge and character-building in a supportive educational environment. These findings contribute to the modern curriculum development that is more adaptive to the needs of today's students. Hopefully, this curriculum can be widely applied to achieve sustainable and holistic educational outcomes.